Synthesis, crystal structure and photoluminescence of a binuclear complex of europium(III) containing 3,5-dicarboxypyrazolate and succinate - Lahoud, Marcelo G. [UNESP]; Marques, Lippy F.; Da Silva, Patrícia B. [UNESP]; De Jesus, Caio A.S. [UNESP]; Da Silva, Cecilia C.P.; Ellena, Javier; Freitas, Rafael S.; Davolos, Marian Rosaly [UNESP]; Frem, Regina C.G. [UNESP] (Elsevier, 2013)
The new europium binuclear complex [Eu2(dcpz) 2(suc)(H2O)8]·(H2O) 1.5 (dcpz = 3,5-dicarboxypyrazolate and suc = succinate) has been synthesized and structurally characterized by single crystal X-ray diffraction methods. The binuclear complex crystallizes in the triclinic space group P1̄ and consists of two lanthanide ions linked by two different bridging organic ligands. 3D supramolecular framework is constructed by hydrogen bonds. The compound shows strong red emission under UV excitation at room temperature associated to IL transitions indicating a ligand to metal energy transfer mechanism since the triplet energy level lies higher than that of europium 5D0 level. Magnetic susceptibility studies showed weak temperature dependence characteristic of the Van Vleck paramagnetism. © 2013 Elsevier Ltd. All rights reserved.
Keywords: 3,5-Dicarboxypyrazolate; Europium(III) ion; Succinate